1988
DOI: 10.3354/meps046171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of community attributes of the benthic meiofauna of Frierfjord/Langesundfjord

Abstract: Sublittoral meiofauna was sampled for the GEEP Workshop along a putative pollution gradient at 6 sites in FrierfjordlLangesundfjord, Norway. Data were subjected to mutivariate statistical analyses which discriminate between sites on their faunlstic attributes, and univariate measures of community stress were determined. Most mulhvariate techniques produced similar results. The copepod component of the meiofauna discriminated between sites better than the nematodes at the species level, but nematodes were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
7

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 18 publications
(16 reference statements)
5
58
1
7
Order By: Relevance
“…Moreover, many studies on meio-and macro-benthic disturbance have shown that very little information is lost by working at a taxonomic level higher than species (e.g. family or even phylum; see Heip et al, 1988;Herman & Heip, 1988;Warwick, 1988; Seasonal analysis for short-term impact studies F. Alves et al 4180.3 Journal of the Marine Biological Association of the United Kingdom (2003) Figure 2. Representative view of a Portuguese clam dredge (according to Monteiro, 1985).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Moreover, many studies on meio-and macro-benthic disturbance have shown that very little information is lost by working at a taxonomic level higher than species (e.g. family or even phylum; see Heip et al, 1988;Herman & Heip, 1988;Warwick, 1988; Seasonal analysis for short-term impact studies F. Alves et al 4180.3 Journal of the Marine Biological Association of the United Kingdom (2003) Figure 2. Representative view of a Portuguese clam dredge (according to Monteiro, 1985).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…These include their small size and high densities, so that smaller samples may be collected, shorter generation times and no planktonic phase in their life cycles, suggesting a potentially shorter response time and higher sensitivity to anthropogenic disturbance (Heip et al 1988, Warwick 1993. Heavy metals are an important component in many marine discharges, including sewage, industrial wastes and mining wastes (Bryan 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Newer methods have been suggested such as the distribution of individuals among species (Gray & Pearson 1982), and species abundance : biomass comparisons (ABC) (Warwick 1986), but only a few comparative studies have been done (Gray et al 1988, Heip et al 1988, Warwick 1988). Here we O Inter-Research/Printed in F. R. Germany explore use of a variety of techniques and compare these with multivariate analyses.…”
Section: Introductionmentioning
confidence: 99%